The degree of practicing ethical leadership by private secondary school Principals and it relation to the Organizational Commitment of teachers' from their point of view - daradkeh, Amjd; Al-dajani, Yasmeen; Dauad, Hanaa (Journal of Educational and Psychological Sciences, 2020)
The current study aims to identify the degree of practicing ethical leadership by the principals of private secondary schools in the capital, Amman and its relationship to the organizational commitment of the teachers from their point of view. In order to achieve the goals of this study the descriptive associative approach has been applied on a sample which consists of (370) teachers who work in private high schools. The results of the study showed the following: The degree of practicing ethical leadership obtained a total average of (3.24 out of 5), while the practice of organizational commitment obtained a total average of (3.27 out of 5) where both came with an average score, at the level of fields, attributes, personal moral qualities got the highest average of (3.40), then in the area of human relations with an average of (3.25) and thirdly came the field of ethical administrative relations with an average of (3.10) and all of them with rated average as for the areas of the commitment axis, the field of responsibility towards the school got the highest average of (3.46 ), followed by the directional commitment with an average of (3.29 ), and finally the continuity commitment with an average of (3.10), all of them with an average estimate.The study used two surveys: the first survey of the ethical leadership consists of (36) items divided on (personal ethical and moral characteristics, ethical- administrative characteristics, human relationships). The second survey of the organizational commitment consists of (23) items divided on (directional commitment, continuing commitment, responsibility towards the school).The validity and reliability of the two studies has been verified, furthermore, they indicated that the degrees of practicing ethical leadership and organizational commitment was moderate, and there is a positive relationship statistically significant at the significance level (α
Keywords: Ethical leadership; organizational commitment; teachers; Capital Amman